A diferença na formação profissional entre arquivista e bibliotecário: por meio de observação nas atividades curriculares da UFPA - SILVA, Tatyana Sousa da (2017)
The present work aimed to analyze and point out the differences between archivists and librarians through their training at the Federal University of Pará, as well as to identify similarities and differences in the curricula offered at the institution. For this purpose, bibliographical and documentary research was used as a method for collecting data, through a study based on the theoretical reference on professional differences.